Heterogeneidade espacial e variação temporal do microclima e seus efeitos sobre a ocorrência de três espécies de marsupiais na Mata Atlântica - Aprigliano, Paula (2003)
The spacial heterogeneity and the temporal variation of the biotics and abiotics characteristics of the environment influence the distribution of animal species. Therefore, the interactions between the climatic conditions and the structure of the environment are important in any study that evaluate the dynamics and the ecological processes of a region. The aim of this study is to evaluate the space and time variations of the microclimate, its effect on the microhabitat and consequentely on the dynamics of the populations of small mammals, in an area of Atlantic Forest. Also a method of evaluation of the microclimate variables (temperature, humidity and luminosity) was developed, where were used data loggers, a programmed reading equipment of climatic parameters. To characterize the microhabitat were measured eight variables proposed in Freitas et al. (2002). The developed and tested method is efficcient in the study of environment of small mammals that live in this layer of air near the ground. The results show spacial and temporal differences of the studied variables, where the spacial variatuon of the microclimate could be attributed to the differences of altitude and in the local structural, and, its temporal variation affects the dynamics of the microhabitat. Models of habitat preference were found for the marsupials Didelphis aurita (generalist with good capacity of local maintenance) and Metachirus nudicaudatus (developed understory and lesser capacity of local maintenance), while Marmosops incanus presented correlation with the microclimate, occurring with bigger populations in the highest places of the study area, with lower temperatures and higher relative humidity.